Analisis Perancangan Tebal Perkerasan Lentur Pada Ruas Jalan Luar Lingkar Selatan Kabupaten Kotawaringin Timur: Design Analysis Of Flexible Pavement Thickness On The South Outer Ring Road Section Of East Kotawaringin Regency - Yosevina Yosevina; Prihanika Prihanika (Media Ilmiah Teknik Sipil, 2026)
Roads, as one of the means of land transportation, are used by road users as connecting routes from one place to another and also play a very important role in boosting economic activities in a location. Therefore, it is very necessary to increase the capacity of road sections in order to meet transportation needs, enabling access to smaller areas and improving the quality of life of the community. During surveys conducted at certain points, these roads were found to be in very concerning conditions. The road damage includes potholes, which can disturb the safety and comfort of the road users. In the planning, this road pavement will be handled for a length of 2 km. In this study, the author conducted calculations using the Component Analysis Method to determine the thickness of flexible pavement. The results of the research and data analysis using the Component Analysis Method revealed a flexible pavement thickness consisting of a 13 cm surface layer, 20 cm Class A LPA, and 15 cm Class B LPA.